Trois blenniidae nouveaux pour la faune du Portugal (Pisces: Perciformes) - Almeida, Armando J. (1980)
The presence of Blennius pilicornis Cuvier, 1829, Blennius incognitus Bath, 1968 and Blennius dalmatinus Steindachner & Kolombatovic, 1883, in portuguese waters ir recorded here for the first time. The authors consider var. maroccana Collignon & Aloncle, 1973, of Blennius goreensis Valenciennes 1835 to be a recent synonym of B. pilicornis Cuvier, 1829. The eggs and the youngest larval stage of B. pilicornis Cuvier 1829 are described for the first time. Ecological data and meristic data are given for each species